2008
DOI: 10.1254/jphs.fm0070218
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Topics of Bone Metabolism: Recent Advances in Pharmacological Management of Osteoporosis

Abstract: Abstract. The prevention of osteoporotic fracture is an essential socioeconomical priority, especially in the developed countries including Japan. Estrogen, selective estrogen-receptor modulators (SERMs), and bisphosphonate are potent inhibitors of bone resorption; and they have clinical relevance to reduce osteoporotic fractures in postmenopausal women. However, we can prevent at most 50% of vertebral fractures with these agents. For the better compliance of aminobisphosphonate, the use of a daily bisphosphon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 42 publications
0
17
0
3
Order By: Relevance
“…Postmenopausal women generally lose bone due to diminished ovarian estrogen and a subsequent increase in bone resorption (32,48). Previous studies have shown that inflammatory cytokines such as interleukin (IL)-1 and prostaglandin E 2 (PGE 2 ) may be involved in the mechanism of bone loss attributable to estrogen insufficiency (49e51).…”
Section: Discussionmentioning
confidence: 99%
“…Postmenopausal women generally lose bone due to diminished ovarian estrogen and a subsequent increase in bone resorption (32,48). Previous studies have shown that inflammatory cytokines such as interleukin (IL)-1 and prostaglandin E 2 (PGE 2 ) may be involved in the mechanism of bone loss attributable to estrogen insufficiency (49e51).…”
Section: Discussionmentioning
confidence: 99%
“…The proper balance between bone formation and resorption is regulated by various hormones and cytokines that modulate bone metabolism. If this balance is disrupted, metabolic bone diseases such as osteoporosis and osteopetrosis result (4,5). Osteoclasts are members of the monocyte/macrophage lineage and are formed by fusion of their mononuclear cellular precursors.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the rapid increase in the elderly population means that the prevention of osteoporotic fracture is a socioeconomic priority [Suzuki et al 2008]. …”
Section: Introductionmentioning
confidence: 99%